Avaliação longitudinal de lesões cariosas inativas em molares permanentes: resultados de 4-5 anos - Dalla Nora, Ângela (2016)
The aim of this dissertation is to present a resulting article from a prospective cohort study. We evaluated the clinical behavior and the progression risk of non cavitated and minimally cavitated inactive carious lesions on the occlusal surfaces of permanent molars over 4-5 years. The estimated sample size was 250 students who were selected by convenience among children attending a school in the municipality of Santa Maria. Initially, the presence of plaque accumulation and carious lesion on the occlusal surfaces of permanent molars was assessed, as well as their eruption stage. The exact location of carious site was recorded by means of drawings the occlusal surfaces to ensure the monitoring of the same lesion over time. After 4-5 years, another clinical examination was performed according to the baseline examination by an examiner who was blinded in regards to the teeth situation at the first examination. Categorical data were described by absolute and relative frequencies (rates). Logistic regression model adjusted for data clusters was used to estimate the incidence/progression of caries. From 258 children, a total of 193 (74.8%) with a mean age of 17.9 (±2.9) years were examined after 4-5 years. When evaluating the progression of lesions considering the criterion of "Activity", 30.6% (n=59) of the sample had at least one molar with active lesion, filled or extracted. For this criterion, inactive lesions had around a 2-fold higher chance of progression when compared to sound surfaces (OR=2.34; IC 95% = 1.51-3.62). Based on the "severity" criterion, 13% (n=25) of the sample had at least one molar that progressed to dentin cavity, filling or extraction. Inactive carious lesion also had a significantly higher chance of progression when compared to sound surfaces according to this criterion (OR = 2.69, 95% CI = 1.50-4.83). In conclusion, this longitudinal study showed that the vast majority of lesions (85-90%) identified as inactive enamel caries at baseline have not progressed over 4-5 years. Despite this fact, it was possible to detect an increased risk for caries progression in caries-inactive occlusal sites compared with the sound ones.